An institutional analysis of glacial floods and disaster risk management in the Nepal Himalaya. (August 2020) - Thompson, Ian; Shrestha, Milan; Chhetri, Netra; Agusdinata, Datu Buyung
Abstract: Institutional factors of disaster risks have rarely been studied for glacial lake outburst floods (GLOFs), which are threatening high mountain regions such as the Andes, Alps, and Himalayas. Exacerbated by climate change, much of the focus in the Himalayas so far has been on GLOF risk anticipation. Recent research suggested the gaps in how scientific information on GLOFs has been communicated to local communities and the resulting distrust in government-led mitigation efforts such as, lake lowering and early warning systems. These gaps are largely driven by a set of socio-economic, cultural and institutional factors, which are poorly understood. Applying an institutional analysis framework, this research examines the institutional conditions under which Himalayan communities can create effective strategies to address GLOF risks. This research applies a mixed-methods approach by combining a) quantitative analysis of household social surveys, and b) qualitative analysis that maps out the various institutional factors that influence the success of community-level mitigation efforts. Additionally, GLOF case studies from Nepal are compared to those of Peru, where a long history of managing GLOFs exists. A set of critical institutional factors and barriers have been identified, including lack of cross-scalar communication networks, a mismatch between the agenda of external agencies and priorities of local communities, failure to recognize the value of local knowledge and participation in policy processes, and ineffective inter-organizational coordination of knowledge sharing and funding streams for mitigation projects. Bridging these disconnects is a significant step toward successful adaptation and mitigation efforts to reduce future GLOF disaster risks.